2009
DOI: 10.3855/jidc.20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of select respiratory tract pathogens in Dakar, Senegal

Abstract: Background : Haemophilus influenzae, Moraxella catarrhalis, Streptococcus pyogenes, and Streptococcus pneumoniae are the most common causative agents of respiratory tract infections (RTIs). The increase in resistance to current antibacterial agents highlights the need to monitor the resistance pattern of these bacterial pathogens. Methodology: In this study, we assessed the antibacterial susceptibility of these pathogens causing respiratory tract infections in Dakar, Senegal, during 2007. A total of 290 bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
2
7
3
Order By: Relevance
“…This suggests that beta-lactamase production could be the major mechanism of antibiotic resistance for these organisms. A high rate (100%) of H. influenzae resistance to cotrimoxazole was observed, contrasting therefore with results reported by Gueye et al, in Dakar in 2009 (10).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This suggests that beta-lactamase production could be the major mechanism of antibiotic resistance for these organisms. A high rate (100%) of H. influenzae resistance to cotrimoxazole was observed, contrasting therefore with results reported by Gueye et al, in Dakar in 2009 (10).…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, high resistance rate (31.3%) of S. pneumoniae to penicillin G was observed, which is similar to data previously reported in a study conducted by Gueye and al. in Dakar (10). However, our data are not consistent with results reported in Sub-Saharan Africa in which resistance level remained below 6% overall (12).…”
Section: Articlecontrasting
confidence: 57%
See 1 more Smart Citation
“…The penicillin susceptibility of GAS has not altered significantly in over 50 years of use of penicillin as a treatment for GAS infection (467). Reported MIC 90 values of penicillin are a median of 0.016 mg/liter and a range of 0.0025 to 0.032 mg/liter (467)(468)(469)(470)(471). There has been only a single report of naturally occurring penicillin-tolerant GAS (472); however, this report has not been independently confirmed.…”
Section: Antibiotic Resistance Penicillin Sensitivitymentioning
confidence: 87%
“…A surveillance study of community-acquired respiratory pathogens during the 2005-2006 respiratory season in the USA reported that the rate of resistance to azithromycin was 34% [16], and data from Senegal in West Africa [17] indicated that <5% of all S. pneumoniae isolates were resistant to macrolides. In Japan [6], however, rates of erythromycin-resistant S. pneumoniae strains ranged from 77.2% to 81.9% during the 1999-2004 respiratory seasons, and MIC 50 values for macrolides against S. pneumoniae were 128 mg/L (azithromycin and erythromycin) and 64 mg/L (clarithromycin).…”
Section: Discussionmentioning
confidence: 99%